2013
DOI: 10.1371/journal.pone.0056745
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Its Association with Critical Limb Ischemia in PAOD Patients

Abstract: BackgroundThe Neutrophil-to-Lymphocyte ratio (NLR) is an easy to perform test from the white blood cell count. An increase in NLR has been associated with vascular endpoints reflecting inflammation in atherosclerotic lesions. Atherosclerosis is a global threat and vascular endpoints, like myocardial infarction or critical limb ischemia (CLI), are a leading cause of death in industrialized countries. We therefore investigated NLR and its association with CLI and other vascular endpoints in peripheral arterial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 18 publications
6
67
4
1
Order By: Relevance
“…Since increasing neutrophil count reflects inflammation and lower lymphocyte counts may reflect general stress and malnutrition, NLR is hypothesized to be more sensitive at detecting patients at high risk for CVD. Indeed, NLR has been found to be a valuable index for predicting adverse clinical outcomes and estimates survival in various clinical settings in oncology [5] and cardiology practices [6][7][8]. Moreover, recently, NLR was associated with loss of renal function [9] and endothelial dysfunction [10] in CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since increasing neutrophil count reflects inflammation and lower lymphocyte counts may reflect general stress and malnutrition, NLR is hypothesized to be more sensitive at detecting patients at high risk for CVD. Indeed, NLR has been found to be a valuable index for predicting adverse clinical outcomes and estimates survival in various clinical settings in oncology [5] and cardiology practices [6][7][8]. Moreover, recently, NLR was associated with loss of renal function [9] and endothelial dysfunction [10] in CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, NLR was found to be associated with the severity of coronary artery disease and 30year survival (7). In patients with peripheral arterial disease NLR was associated with ischemic event risk (9). In a cross-sectional study in 2013, NLR was positively correlated with IL-6 and CRP while negatively correlated with serum albumin levels in predialysis and dialysis patients.…”
Section: Discussionmentioning
confidence: 97%
“…Inflammation has a central role in the pathogenesis of atherosclerosis (13). NLR is being used as a new inflammatory marker in many diseases to identify higher risk patients (7)(8)(9)16,17). In a study, NLR was found to be associated with the severity of coronary artery disease and 30year survival (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR is being widely used to identify high-risk patients with various illnesses, including cancer [39] and CVD [39][40][41][42] . In our paper, we discussed NLR and clinical outcomes in patients with ESRD.…”
Section: Potential Role Of Nlr As An Inflammatory Biomarkermentioning
confidence: 99%